Respuesta :

Step-by-step explanation:

[tex] \frac{dy}{dt} = \frac{t}{ {t}^{2} y + y} [/tex]

[tex] \frac{dy}{dt} = \frac{t}{y( {t}^{2} + 1) } [/tex]

Using seperation by variables,

[tex]ydy = \frac{t}{ {t}^{2} + 1 } dt[/tex]

Integrate both sides, for the left side, use the power rule, we get

[tex] \frac{y {}^{2} }{2} [/tex]

For the right side, let

[tex]u = {t}^{2} + 1[/tex]

[tex]du = 2tdt[/tex]

[tex] \frac{du}{2} = tdt[/tex]

So we get, on the right side

[tex] \frac{1}{2} ln( |t {}^{2} + 1 | ) + c[/tex]

As of right now, we have

[tex] \frac{ {y}^{2} }{2} = \frac{1}{2} ln( {t}^{2} + 1) + c[/tex]

Solving for y, gives us

[tex] {y}^{2} = ln( {t}^{2} + 1 ) + c[/tex]

[tex]y = \sqrt{ ln( {t}^{2} + 1) + c} [/tex]

Plugging in t=0, gives us

[tex]2 = \sqrt{ ln(1) + c } [/tex]

[tex]2 = \sqrt{c} [/tex]

[tex]4 = c[/tex]

So. our formula is

[tex]y = \sqrt{ ln( {t}^{2} + 1 ) + 4 } [/tex]